Peningkatan Hasil Belajar Matematika Siswa dengan Menerapkan Model Pembelajaran Talking Stick - Isnaeni Isnaeni; Muhaemin Muhaemin; Hasri Hasri (Prodi Pendidikan Matematika FTIK IAIN Palopo, 2017)
This article aims to see the improvement of students' mathematics learning outcomes by using the talking stick teaching model. The type of research used is classroom action research designed two cycles in accordance with the achievement of indicators. The subjects are all students of class VIII Madrasah Tsanawiyah No 32 Lamasi Kecamatan Lamasi Kabupaten Luwu, amounting to 21 people. The instruments used were test and observation. Before treatment, the average student's learning outcomes of 50.95. If associated with the indicator of success is 70, then the student is not yet complete in learning mathematics. This is also an indication that there is a problem in learning mathematics in that class. After the applied model of talking stick, the average value of students increased in cycle I to 65.23 but there are still 11 students who have not completed. The study then continued to cycle II and the average of mathematics learning outcomes increased to 80.38 with 17 students already completed or 80.95%. If it is associated with the indicator where the research is said to be successful if the students who get a minimum score of 70 amounted to at least 80% then this research has been successful and stopped until the second cycle. Student and teacher activity also showed positive results. From the observation seen there is improvement of mental attitude of student in expressing its opinion from 57,1% student increase to 85,7%. The same for student responses in answering teacher questions increased from 52.3% to 90.4%. Teacher activity increased slightly from 50.0% to 50.84%. Of all the results it is clear that the learning model of talking stick can improve students' mathematics learning outcomes.